KNOWLEDGE DAN TALENT MANAGEMENT DALAM MENINGKATKAN KINERJA ORGANISASI PUBLIK - Herawati, Augustin Rina (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2008)
Organizations have to adjust to the rapidly-changing, global era so as to remain existing. There are several strategies organizations may take in order to survive. One of them is through the implementation of knowledge and talent management system. This strategy emphasizes the cooperation of talented and knowledgeable human resources for achieving better organization performance, or better processes at work.